2022
DOI: 10.3389/fpsyg.2022.901247
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mindfulness-Based Stress Reduction (MBSR) on Psychological Outcomes and Quality of Life in Patients With Lung Cancer: A Meta-Analysis

Abstract: ObjectiveThe impact of the mindfulness-based stress reduction (MBSR) program on psychological outcomes and quality of life (QoL) in lung cancer patients remains unclear. This meta-analysis aimed to evaluate the effectiveness of the MBSR program on psychological states and QoL in lung cancer patients.MethodsEligible studies published before November 2021 were systematically searched from PubMed, EMBASE, Cochrane Library, PsycINFO, China National Knowledge Infrastructure (CNKI), and Wanfang databases. The risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…We estimated the sample size using psychological distress as the main effect indicator for this study. According to our previous meta-analysis, 45 the MBSR program was associated with an effect size of 0.418, which was estimated based on the pooled result of psychological distress. Therefore, we estimated a theoretical sample size of 75 cases to ensure a statistical power of 80.0%.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We estimated the sample size using psychological distress as the main effect indicator for this study. According to our previous meta-analysis, 45 the MBSR program was associated with an effect size of 0.418, which was estimated based on the pooled result of psychological distress. Therefore, we estimated a theoretical sample size of 75 cases to ensure a statistical power of 80.0%.…”
Section: Methodsmentioning
confidence: 99%
“…Participants in the experimental group received both usual care and a 4-week MBSR program. In this study, we selected a 4-week MBSR program as an intervention according to our meta-analysis 45 because patients with lung cancer usually have a relatively short median survival time and fast deterioration in physical health. 59 During this 4-week MBSR program, all participants in the experimental group practiced MBSR under the guidance and supervision of a psychologists qualified as mindfulness trainer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with lung cancer are more likely to suffer from psychological distress than patients with other types of cancer (Tian et al, 2021a). The reported prevalence of psychological distress in lung cancer patients ranges from 17.0-73.0% (Tian et al, 2023), and a recent meta-analysis revealed that the average prevalence of psychological distress in Chinese lung cancer patients was 48.3% (Chen et al, 2021). Psychological distress can lead to adverse symptoms such as depression, anxiety, and sleep disturbance, which can interfere with patients' ability to cope with anti-cancer treatment (Tian and Jimenez-Herrera, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The reported prevalence of psychological distress in lung cancer patients ranges from 17.0-73.0% (Tian et al, 2023), and a recent meta-analysis revealed that the average prevalence of psychological distress in Chinese lung cancer patients was 48.3% (Chen et al, 2021). Psychological distress can lead to adverse symptoms such as depression, anxiety, and sleep disturbance, which can interfere with patients' ability to cope with anti-cancer treatment (Tian and Jimenez-Herrera, 2023). An experimental study even showed that psychological distress may enhance tumor growth and diminish effective response to anti-cancer treatment, as well as decrease therapeutic potential (Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%